The production and reproduction of the body: an analysis of healthy living digital influencers - Viotto, Marina Henriques (2019)
In this dissertation, my aim is to understand how the body is socially produced and reproduced. To do this, I investigate the empirical context of healthy living in two ways: by exploring digital influencers through their Instagram profiles and by interviewing 11 female consumers that follow these influencers online. Throughout this investigation, I noticed that there were two separate paths of analysis, which are related to taste transformation and to societies of control. As such, I have developed two research articles in this dissertation. In the first article, my aim is to understand the role of the body in taste transformation process, giving the body a more central position in the advancements of taste theorization. I found that transforming taste by adopting the practices of a taste regime changes the ways in which consumers display distinction, being the body the main element for triggering taste transformation. Then, in the second article, my aim is to understand how performative devices (i.e., digital platforms) enable societies of control and the controlled body. As I focus on the concept of societies of control, I show that the body is a key site for control to take place. As such, I also show that performative devices, individuals, and content generated online interact in such a way that they constitute the lifestyle-controlling assemblages, networks of elements that enable the control of lifestyles and its associated body shapes.